1994
DOI: 10.1016/0009-2614(94)00440-4
|View full text |Cite
|
Sign up to set email alerts
|

Orientation dependence of NO sticking and scattering at Pt (100)

Abstract: Gas-phase oriented NO molecules are focused onto a Pt( 100) surface in a supersonic molecular beam. The total number of the scattered and desorbed NO molecules is determined from recordings of the relative partial NO pressure. This signal shows a strong dependence on the initial NO orientation (preferential Nend or O-end collisions) and surface temperature. Apart from a direct chemisorption channel, the results show that there may be an orientation-dependent effect for the NO molecules trapping into a precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…For spectroscopic reasons, such experiments are particularly well suited to the NO molecule. [2][3][4][5][6][7][8][9][10][11][12][13] The measured features resulting from the scattering experiments cannot directly be linked to the potential energy surface. Molecular dynamics ͑MD͒ simulations can give insight how those features are connected to properties of the potential energy surface and provide detailed information on the dynamical processes of the gas-surface interaction.…”
Section: Introductionmentioning
confidence: 99%
“…For spectroscopic reasons, such experiments are particularly well suited to the NO molecule. [2][3][4][5][6][7][8][9][10][11][12][13] The measured features resulting from the scattering experiments cannot directly be linked to the potential energy surface. Molecular dynamics ͑MD͒ simulations can give insight how those features are connected to properties of the potential energy surface and provide detailed information on the dynamical processes of the gas-surface interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we target measurements at high kinetic energy to have the best chance of avoiding the obscuring effects of dynamical steering. Moreover, the experiment is further simplified at high kinetic energy as these conditions suppress sticking (20), an elementary surface process where strong orientation effects have been previously reported (21)(22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…In the reactive NO=Pt111, the trapping probability is higher for the N end than for the O end [2]. The sticking probability of NO on reactive Ni(100) and Pt(100) also demonstrated that the N end is more reactive than the O end [3,5,7]. Moreover, clear steric effects have been observed in the gas-phase products for the (NO CO) reactions on Pt(100) [6].…”
mentioning
confidence: 96%
“…The steric effect, reactant orientation, and alignment, are of great importance in surface chemistry [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The stereodynamics of NO on a surface has been a particular target of several studies using various experimental approaches [1][2][3][4][5][6][7].…”
mentioning
confidence: 99%
See 1 more Smart Citation